E2F1 copy number variations contribute to spermatogenic impairment and cryptorchidism by increasing susceptibility to heat stress. (18th January 2019) - Rocca, M. S.; Di Nisio, A.; Sabovic, I.; Ghezzi, M.; Foresta, C.; Ferlin, A.
Abstract: Background: Copy number variations (CNVs) play an important role in the onset of several diseases, and recently research focused on the relationship between these structural variants and diseases of the reproductive tract, including male infertility and cryptorchidism. Objectives: To evaluate the contribution of copy number variations of E2F1 gene to idiopathic male infertility and the factors influencing expression of this gene. Materials and Methods: We performed a retrospective study on 540 subjects recruited from September 2014 to February 2015. TaqMan CNV assay was used to analyze E2F1 CNV. Real‐time PCR was used to assess E2F1 and HSP70 expression level in heat stressed and transfected cells with three E2F1 copies. Results: We found a significant difference in the frequency of altered E2F1 copies in patients (12/343, 3.5%) compared with controls (0/197) ( p = 0.005). Six patients with E2F1 CNV had history of cryptorchidism, but the prevalence between men with idiopathic infertility (6/243, 2.5%) and infertile men with history of cryptorchidism (6/100, 6.0%) was not statistically different ( p = 0.1). E2F1 expression increased under heat stress conditions, especially in cells carrying more copies of gene and this was associated with increased expression of HSP70. Discussion: Our data suggest that an abnormal E2F1 expression caused by multiple copies of E2F1 gene predisposes to the onset of infertility and that the risk further increases if subjects with altered E2F1 copies have stressful conditions, such as heat stress or history of cryptorchidism. Conclusion: This study shows a link between E2F1 CNV and male infertility, suggesting that the increased risk of spermatogenic impairment associated with higher E2F1 copies might be due to higher susceptibility to stressful conditions.